SIRASS: sistema de rastreamento de smartphone - Kieltyka, Valmir (2013)
The emergence of new technologies allows the development of new systems that contribute to the technological advance. The need to keep available and connected to the web all time makes us to walk with technological devices in the pocket day and night, thus being accessible at any time. This work aims to create a system for locating mobile Smartphones, using the Android platform to develop an application with geoprocessing capabilities, applied to locate and track mobile devices.